1998
DOI: 10.1038/sj.onc.1202443
|View full text |Cite
|
Sign up to set email alerts
|

pRB phosphorylation mutants reveal role of pRB in regulating S phase completion by a mechanism independent of E2F

Abstract: Progression of cells into S phase is controlled by the retinoblastoma protein (pRB) and relies on the functional inactivation of this tumour suppressor in late G1 via protein phosphorylation. We provide evidence here that, besides controlling entry of cells into S phase, pRB can operate to inhibit S phase completion. Dierential arrays of phosphorylation appear to regulate these dierent events, suggesting that cycle progression at these two stages of the cell cycle may be achieved via activation of distinct dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
94
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 34 publications
7
94
0
Order By: Relevance
“…However, E2F is not su cient to prevent growth inhibition by p27, implying that cyclin E/CDK2 complexes have an additional role(s) at the G1-S transition, distinct from pRb phosphorylation (Alevizopoulos et al, 1997;Mann and Jones, 1996). Similar conclusions were reached by other groups (Chew et al, 1998;Hofmann and Livingston, 1996;Knudsen et al, 1998;Leng et al, 1997;Lukas et al, 1997;Ohtsubo et al, 1995;Resnitzky and Reed, 1995). In summary, the ability of the CDK4 inhibitor p16 to arrest the cell cycle in G1 seems to depend essentially on activation of pRb and sequestration of E2F, whereas p27 not only activates pRb, but also impinges on other CDK2-regulated events (discussed in Dyson, 1998).…”
Section: Introductionsupporting
confidence: 86%
“…However, E2F is not su cient to prevent growth inhibition by p27, implying that cyclin E/CDK2 complexes have an additional role(s) at the G1-S transition, distinct from pRb phosphorylation (Alevizopoulos et al, 1997;Mann and Jones, 1996). Similar conclusions were reached by other groups (Chew et al, 1998;Hofmann and Livingston, 1996;Knudsen et al, 1998;Leng et al, 1997;Lukas et al, 1997;Ohtsubo et al, 1995;Resnitzky and Reed, 1995). In summary, the ability of the CDK4 inhibitor p16 to arrest the cell cycle in G1 seems to depend essentially on activation of pRb and sequestration of E2F, whereas p27 not only activates pRb, but also impinges on other CDK2-regulated events (discussed in Dyson, 1998).…”
Section: Introductionsupporting
confidence: 86%
“…Note that the di use nuclear BCL6fg staining (visible on Figures 1c and Figure 8a), but not the nuclear dots, largely disappears upon the`pre-permeabilization' procedure (before formalin ®xation) used in this experiment (see Materials and methods) Growth suppression and apoptosis by BCL6 (LAZ3) O Albagli et al Albagli et al, 1998;Foley et al, 1998 and references therein). Of particular interest is the case of RB, which inhibits both the entry and the progression through S phase (Brehm et al, 1998;Chew et al, 1998;Knudsen et al, 1998;Luo et al, 1998;MagnaghiJaulin et al, 1998 and references therein). On the contrary, certain histone acetyltransferases may facilitate the progression in the cell cycle, as P300 undergoes an activating phosphorylation at the G1/S boundary (Ait-Si-Ali et al, 1998) while mice lacking P300 have defects in cell proliferation (Yao et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian cDNA expression vectors for PML, PLZF, 5 0 PLZF (encoding amino acids 1-455 of PLZF, but lacking the last seven C-terminal zinc-fingers), poxvirus and zinc-finger (POZ) domain (encoding the N-terminal amino acids 1-120 of PLZF) and the GST-PLZF plasmid have been previously described (Chen et al, 1994;Dong et al, 1996;Guidez et al, 1998). Expression vectors for E2F1 (Hsieh et al, 1997), Rb (Chew et al, 1998) and GST-Rb (full-length and deletions) (Zarkowska and Mittnacht, 1997) have also been previously described. (Figure 1c).…”
mentioning
confidence: 99%
“…This is facilitated through selective partnering with other transcription factors, which in turn bring promoters with combinatorial binding sites under E2F and, hence, Rb control (Schlisio et al, 2002; Figure 4 Co-expression of retinoblastoma (Rb) and promyelocytic leukemia zinc-finger (PLZF) enhances transcriptional repression of PLZF and E2F1/Rb target genes. C33A cells were transiently transfected (Lipofectamine 2000, Qiagen) with luciferase reporters containing (a) three copies of an E2F consensus binding sequence along with mammalian expression plasmids encoding PLZF, phosphorylation-deficient Rb protein (Rb NPC ) or E2F1 and DP1 as indicated (Chen et al, 1994;Chew et al, 1998) or (b) a PLZFresponsive Hoxb2 r3/r5 enhancer luciferase reporter (Ivins et al, 2003) along with PLZF and Rb NPC as indicated. Cells were harvested 36 h after transfection and luciferase assays performed as previously described (Petrie et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation